Investigation of triamterene as an inhibitor of the TGR5 receptor: identification in cells and animals - Li Y; Cheng KC; Niu C; Lo S; Cheng JT; Niu H (Dove Medical Press, 2017)
Yingxiao Li,1,2 Kai Chun Cheng,1 Chiang-Shan Niu,3 Shih-Hsiang Lo,3,4 Juei-Tang Cheng,2,5 Ho-Shan Niu31Department of Psychosomatic Internal Medicine, Graduate School of Medical and Dental Sciences, Kagoshima University, Kagoshima, Japan; 2Department of Medical Research, Chi Mei Medical Center, Yong Kang, Tainan City, 3Department of Nursing, Tzu Chi College of Technology, Hualien City, 4Division of Cardiology, Department of Internal Medicine, Chung Hsing Branch of Taipei City Hospital, 5Institute of Medical Sciences, College of Health Science, Chang-Jung Christian University, Guei-Ren, Tainan City, TaiwanBackground: G-protein-coupled bile acid receptor 1 (GPBAR1, also known as TGR5) has been shown to participate in glucose homeostasis. In animal models, a TGR5 agonist increases incretin secretion to reduce hyperglycemia. Many agonists have been developed for clinical use. However, the effects of TGR5 blockade have not been studied extensively, with the exception of studies using TGR5 knockout mice. Therefore, we investigated the potential effect of triamterene on TGR5.Methods: We transfected the TGR5 gene into cultured Chinese hamster ovary cells (CHO-K1 cells) to express TGR5. Then, we applied a fluorescent indicator to examine the glucose uptake of these transfected cells. In addition, NCI-H716 cells that secrete incretin were also evaluated. Fura-2, a fluorescence indicator, was applied to determine the changes in calcium concentrations. The levels of cyclic adenosine monophosphate (cAMP) and glucagon-like peptide (GLP-1) were estimated using enzyme-linked immunosorbent assay kits. Moreover, rats with streptozotocin (STZ)-induced type 1-like diabetes were used to investigate the effects in vivo.Results: Triamterene dose dependently inhibits the increase in glucose uptake induced by TGR5 agonists in CHO-K1 cells expressing the TGR5 gene. In cultured NCI-H716 cells, TGR5 activation also increases GLP-1 secretion by increasing calcium levels. Triamterene inhibits the increased calcium levels by TGR5 activation through competitive antagonism. Moreover, the GLP-1 secretion and increased cAMP levels induced by TGR5 activation are both dose dependently reduced by triamterene. However, treatment with KB-R7943 at a dose sufficient to block the Na+/Ca2+ exchanger (NCX) failed to modify the responses to TGR5 activation in NCI-H716 cells or CHO-K1 cells expressing TGR5. Therefore, the inhibitory effects of triamterene on TGR5 activation do not appear to be related to NCX inhibition. Blockade of TGR5 activation by triamterene was further characterized in vivo using the STZ-induced diabetic rats.Conclusion: Based on the obtained data, we identified triamterene as a reliable inhibitor of TGR5. Therefore, triamterene can be developed as a clinical inhibitor of TGR5 activation in future studies.Keywords: triamterene, CHO-K1 cells, TGR5, transfection, sitagliptin